Comparative study of chemoradiation and neoadjuvant chemotherapy effects before radical hysterectomy in stage IB–IIB bulky cervical cancer and with tumor diameter greater than 4 cm. Issue 3 (1st April 2005) - Modarress, M.; Maghami, F. Q.; Golnavaz, M.; Behtash, N.; Mousavi, A.; Khalili, G. R.
Abstract : Tumor size seems to be a determinant in the prognosis of early cervical cancer. Patients with tumor greater than 4 cm (bulky) in diameter have worse outcome. The purpose of this study was to compare the efficacy of preoperative combined chemoradiation and neoadjuvant chemotherapy (NAIC) programs followed by radical hysterectomy in stage IB–IIB bulky cervical cancer. From September 1999 to April 2002, 60 patients with stage IB–IIB bulky cervical cancer were treated with preoperative external-beam radiotherapy to 45 Gy plus weekly cisplatin 50 mg/m 2 or preoperative NAIC by cisplatin 50 mg/m 2 and vincristin 1 mg/m 2 every 7–10 days, for three courses. Surgery was performed 4–6 weeks after the completion of the preoperative treatment. There were no significant difference between age, stage, tumor size, and histopathologic type in two groups ( P > 0.05). Toxicity associated with two treatment methods was usually mild. In chemoradiation group, two patients developed vesicovaginal fistula, and four patients developed long-term hydronephrosis that needed urethral stenting. Before surgery, complete and partial clinical response had no significant difference between two groups ( P > 0.05). After surgery, lymph node and parametrial involvement had no significant difference between two groups ( P > 0.05). In NAIC group, more patients had significantly residual tumor ( P = 0.012), but residual tumor size had no significant difference between two groups ( P > 0.05). Pathologic complete response was significantly higher in chemoradiation group ( P = 0.004). According to the result of this study, it seems that NAIC and chemoradiation had similar effects in survival prognostic factors.